SOCIALIZATION OF ORGANIC AND INORGANIC WASTE THROUGH THE WASTE BANK PROGRAM - Syarifah Farissi Hamama; Maulida Maulida; Suryani Suryani; Hasanah Hasanah; Irma Aryani (ABDIMU: Jurnal Pengabdian Muhammadiyah, 2022)
Garbage is an environmental problem that has no solution until recently. The limited number of Waste Disposal Sites (TPA) in Lamjamee Dayah makes this waste problem more complex. The Waste Bank is one of the alternatives in the waste management strategy. The waste bank is one of the programs that can change the pattern of people's perspectives on waste management. This socialization activity was carried out in Lamjamee Dayah, Aceh Besar. The purpose of this activity is to reduce the accumulation of household waste so that environmental pollution does not occur, as well as utilize waste with the creations and innovations of the surrounding community. The method used is socialization and documentation. The results show that the local community has not yet received the information about the Waste Bank. This socialization activity informs the community that waste bank management provides many benefits to the surrounding community as it turns the environment becomes comfortable, neat, green, and it can also increase the local communitys economic income.